2019
DOI: 10.17221/264/2019-pse
|View full text |Cite
|
Sign up to set email alerts
|

Yielding of two types of maize cultivars in relation to selected agrotechnical factors

Abstract: The study presents the results of field experiments, the aim of which was to assess the yield of maize cultivars with different genetic profiles depending on the method of soil preparation for sowing and the method of NP fertilizer application. The yield and water content in the grain were significantly dependent on changing weather conditions in the growing seasons. Sowing maize into the soil cultivated traditionally (autumn ploughing), stay-green type cultivars and row fertilization positively influenced mai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…In turn, other authors [27,28] found that too high rainfall during the maize growing season reduced the efficiency of nitrogen application through soil erosion and its leaching into the soil profile. The use of row fertilization is a very good solution in maize cultivation [15,29]. This method of fertilizer application results in a higher concentration of the nutrient.…”
Section: Discussionmentioning
confidence: 99%
“…In turn, other authors [27,28] found that too high rainfall during the maize growing season reduced the efficiency of nitrogen application through soil erosion and its leaching into the soil profile. The use of row fertilization is a very good solution in maize cultivation [15,29]. This method of fertilizer application results in a higher concentration of the nutrient.…”
Section: Discussionmentioning
confidence: 99%
“…Unfavourable weather conditions (rainfall deficit) during the growing season hinder nutrient absorption by maize, mainly phosphorus, which leads to growth inhibition. The research results unambiguously show that this unfavourable phenomenon can be almost completely counteracted by localised fertilisation carried out simultaneously with seed sowing (Jagła et al 2019, Szulc et al 2020).…”
Section: Discussionmentioning
confidence: 57%
“…Maize is currently the most productive and prospective cereal plant, which makes good use of nutrients from mineral and organic fertilisers [20,21]. The amount and quality of the harvested maize grain yield are largely determined by agrotechnical [22][23][24] and agroclimatic factors [25,26], with the availability of soil moisture and nitrogen at critical growth stages having relatively large effects [27,28].…”
Section: Discussionmentioning
confidence: 99%